ORAL MUCOSAL LESIONS IN CHILDREN WITH AND WITHOUT CLEFT PALATE: A CASE CONTROL STUDY - Sangar, Sivesh; Ravindran, Vignesh; Ramanathan, Visalakshi (International Journal of Psychosocial Rehabilitation, 2025)
Oral mucosal lesions are conditions affecting the oral cavity; they include candidiasis, recurrent herpetic lesions, recurrent aphthous stomatitis, hairy tongue and lichen planus. Recording and diagnosis of oral mucosal lesion requires a thorough familial history to be taken before proceeding to conduct a complete oral examination. The aim of the study was to determine the prevalence of oral mucosal lesions in children with cleft palate. A study was carried out by collecting data by reviewing patients data and analysing the data of 86000 patients between June 2019 and March 2020 at the private dental institute. The present study consists of 66 children divided into 2 groups: children with cleft palate and children without cleft palate. In both groups, presence of oral mucosal lesions were noted. Absence of oral mucosal lesions in both groups (children with cleft palate and children without cleft palate). The prevalence of oral mucosal lesions was compared for both case and control group were compared by Mann- Whitney U Test which gave a result of p=1.000 .Within the limitations of the study, there is no evidence regarding oral mucosal lesions in children with and without cleft palate.